EVALUASI KINERJA RANTAI PASOK KOMODITAS STEVIA PADA KOPERASI NUSANTARA KIAT LESTARI - Mohamad Fahri Hasan Sidik (Fakultas Pertanian - UMJ, 2018)
Koperasi Nusantara Kiat Lestari (NUKITA) is an agribusiness unit that founded in 2005. NUKITA provides a place for Mulyasari Farmers which is the supplier of stevia raw materials. NUKITA has a role in processing raw material of stevia into a processed product and marketing process. The aim of the research is to find out the stevia’s supply chain process in NUKITA related to item flow, information flow, and financial flow, also to find out the performance evaluation of Stevia’s Supply Chain in NUKITA measured by Balance Scorecard. This research is studied using qualitative research method with descriptive analysis. The result of this research indicates that there are several parties involved in stevia’s supply chain, they are: farmers, Mulyasari Farmer, NUKITA, and consumers. All of the flow contained in stevia’s supply chain is always through NUKITA due to the cooperation that has been agreed between Mulyasari Farmer and NUKITA. The measurement of stevia’s supply chain performance at NUKITA based on financial, customer, internal business process, and learning and growth perspective resulted NUKITA’s main problem exist in the uncertain market and stevia industry. In addition, NUKITA’s stevia business hasn’t been profitable because of the turnover and continuity of product production is still constrained. However, NUKITA has a crucial role in preserving the varieties of stevia Cibodas Manis 3 and empowering Mulyasari Farmer.